2011
DOI: 10.3733/ucanr.7243
|View full text |Cite
|
Sign up to set email alerts
|

Green Onion Production in California

Abstract: Green onions (Allium cepa L.) are produced mainly in Monterey, Riverside, and Ventura Counties, but there is also small-scale production in other parts of the state. Harvest and bunching of this crop is labor intensive, and over the last several years substantial production has moved to Mexico, where the crop is less expensive to produce. Green onions are planted from spring through fall for nearly year-round harvest. CLIMATIC REQUIREMENTS Onions are cool-season biennial plants (requiring two seasons to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Norman, 1992;Anyanwu, 2003). Carlson and Kirby (2005), Qasem (2006) and Smith et al (2011) confirmed that many authors have reported that onion plants are poor weed competitors and the poor competitive ability of the crop with weeds has been attributed to its initial slow growth and lack of adequate foliage to smother weeds. The establishment of optimum population per unit area of the field is reported by (Singh and Singh, 2000) to be an essential factor that leads to maximum yield.…”
Section: Introductionmentioning
confidence: 71%
“…(Norman, 1992;Anyanwu, 2003). Carlson and Kirby (2005), Qasem (2006) and Smith et al (2011) confirmed that many authors have reported that onion plants are poor weed competitors and the poor competitive ability of the crop with weeds has been attributed to its initial slow growth and lack of adequate foliage to smother weeds. The establishment of optimum population per unit area of the field is reported by (Singh and Singh, 2000) to be an essential factor that leads to maximum yield.…”
Section: Introductionmentioning
confidence: 71%